Creating Inclusive and Hospitable Christian Schools: Three Case Studies - Lane, Julie M. (Journal of disability & religion, 2019)
Many Christian schools accept children with special needs. Structures to support, fund, and strengthen such programs are challenging to find. Studies to date reflect how those Christian schools that do accept children with special needs provide special education services. However, studies on how an inclusive and hospitable culture are created within Christian schools do not appear to exist. The authors identify and discusses the current inclusive and hospitable cultures in three Christian schools in the western United States. The authors used a qualitative bounded system case study to identify potential participants. Data collection included website review and archival documents. The primary researcher spent two and a half to three days at each location conducting interviews with multiple stakeholders and making observations in various settings. Perspectives, reported as themes, and practices of inclusion, are identified and are distilled into recommendations for how the Christian schools studied might serve as exemplars for other Christian schools seeking to include children with special needs.